Fostering Continuous Improvement within new product development processes. (1st January 2003) - Caffyn, Sarah; Grantham, Andrew
Much has been written about Continuous Improvement (CI) conceptually and also empirically in manufacturing environments through case studies. More recently, CI has been evaluated in the context of New Product Development (NPD) processes. However, there is little understanding of the practical issues surrounding adoption of CI in NPD processes, and in particular, of the contingent company-specific variables that affect the implementation of "CI enablers". This paper reports on the findings from a research project that applied an action research approach to investigating these variables in real-time NPD environments. Data from this project, from an in-depth study of a medium-sized design and manufacturing company in the UK, indicate that success with NPD CI enablers may be dependent on less problem-oriented thinking involving high levels of understanding about the concepts underpinning CI, such as improvement and learning. We also suggest that facility with a range of practical skills is necessary; for example, deploying problem-solving tools to procedure and process (rather than product), and a positive interventionist management of the implementation program through CI facilitation. The paper concludes by generalising the findings to current theory about CI and, more specifically, organisational learning within NPD as discussed by Bartezzaghi et al.